Assessment of a catchmentwide salmon habitat rehabilitation scheme on a drained river system in Northern Ireland. (10th May 2014) - Kennedy, R. J.; Johnston, P.; Allen, M.
Abstract A catchment‐scale salmon, Salmo salar L., habitat enhancement scheme was developed for the River Main (Northern Ireland) with reference to baseline habitat and electric fishing surveys. In total, 19 separate sites were enhanced using flow deflectors or random boulder addition. Habitat suitability for juvenile salmon increased at enhanced sites following the scheme, and significant changes in underlying physical habitat characteristics (particle size, depth and flow) were detected after the installation of flow deflectors. The overall index of salmon fry recruitment, monitored across the catchment, showed no change between pre‐ and post‐enhancement periods. The mean biomass of salmon evident at individual enhancement sites (5.1 g m−2) was significantly higher than the mean biomass at control sites (1.2 g m−2). Increased densities of >0+ juvenile salmon were associated with enhanced sites relative to controls. Marking studies indicated the potential for long‐range dispersal of juvenile salmon between 0+ (summer) and 1+ (summer) age classes. The potential of the scheme to enhance the local salmon stock was discussed.